Unemployment and International Trade: The Effects of Minimum Wages and Non-Traded Goods in Models representing Western Industrialized Countries and China (in German) - Alfred Sitz; Friedrich Sindermann (FIW - Research Centre International Economics, 2009)
In this paper we investigate "integrated equilibria" of two-country models. Extending the basic framework non-traded goods as well as minimum wages are introduced and their effects on the models' results are studied. Finally, the consequences of three types of labor "shocks" are analyzed.
Keywords: 330